Scoreboard Indicators That Should Be Installed in Order To Pilot the Performance - El figha, A.; Benhrimida, M. (International Journal of Engineering and Technology, 2019)
According to a US study, 70% of the strategic failures aren't due to a lack of vision, but a poor implementation of it. In other words, a strategy needs steering, which needs indicators.However, the battery of indicators that exist and their diversity poses a problem of their relevance for piloting.In other words, a performance must lead in terms of strategy to the identification of a key success factor, guaranteeing the competitive advantage in the sense of Michael PORTER. This amounts to evaluating the performance not as an analysis of the result, but rather as a result of the action of the decision-maker (the manager).Â
Keywords: Strategy; indicator; performance; competitiveness.